The Form of Traditional House of Coastal Area at Tanjung Bumi Bangkalan as The Basic Preservation of Madura Traditional Architecture - M. Safeyah; E. Elviana; N. Takarini; A. Sutejo (Nusantara Science and Technology Proceedings)
The purpose of the research is to find the traditional house form at Tanjung Bumi Bangkalan, thus it can be used as the basis to preserve the traditional architecture of Madura especially Bangkalan. This study is a descriptive research with qualitative method. Data obtained through interviews, photography, measurements, and sketches. Sample taken by purposive sampling. The data analyzed using principle of design that are; unity, balance, proportion, emphasis, and rhythm. Traditional houses in Tanjung Bumi coastal area consist of Bangsal type and Trompesan type. The house has rectangular from. The unity of the building formed by combining column, wall, space, material texture and colour. The house façade formed symmetrically with the point of interest at the roof that dominated the entire form. The proportion of the roof 1.5 times than the size of the house spatial. The space arrangements dominated by Sedana type, which comprise of two rooms. Space arrangements of Sedana type is lined to the side or lined backward. A high aesthetic value is derived from the creation of elements which considering principle of design.